Individual Dietary Diversity Score for Diabetic and Hypertensive Patients in Cote d’Ivoire - Déré KAL; Djohan YF; Koffi KG; Manhan K; Niamké AG; Tiahou GG (International Journal of Nutrition, 2016)
Unlike developed countries, monitoring of the alimentation quality is important in developing countries. In recent years, several methods of assessing food consumption using simple tools the 24-hour diet recall have been proposed. This individual dietary diversity score (IDDS) is a simplified method for assessing the quality of diets, defined as the number of food groups represented in the diet over a period of time. We conducted an individual qualitative food consumption survey based on the 24 hours recall method. It was an Interviewer-administered questionnaire was used to collect information.The classification terciles of Dietary Diversity score was obtained from the 14 food groups recommended by FAO. 200diabetic and 200 hypertensive patients regularly followed in the same hospital (University hospital of Treichville) were included in this study without any distinction about treatment. The average of individual dietary diversity score was to 5.6 ± 1.58 for diabetic against 6 ± 1.94 food groups consumed the day before by hypertensive. Hypertensive patients in our study seemed o better diversity their diet with 8% of them who had a high score against 0.5% for diabetic. The food groups most consumed by our population were cereals, white tubers, other vegetables, fish and oils and fats at the expense leafy vegetables, vitamin A fruits, other fruits and legumes, nuts and seeds. In terms of anthropometric factors, we found the influence of waist circumference on food diversification in diabetic and not from hypertensive. Considering the importance of dietary diversity to nutrition and health, these results show the need to mobilize efforts for ensuring that people have better access to and knowledge about adequate nutrition. Despite the fact that this study has to be performed and that comparisons with other countries are required to harmonize the methodology, our results show the interest of the use of a simple tool to assess the quality of the food within the population. Using of this tool is certainly a future solution for a rapid diagnostic of diets quality.
Keywords: Dietary Diversity Score